ASSISTED NATURAL REGENERATION AS A CLIMATE-RESILIENT STRATEGY FOR RESTORING DEGRADED PEATLAND FORESTS IN CENTRAL KALIMANTAN - Hakim, Dani Lukman; Lima, Lucas; Mendes, Clara (Yayasan Adra Karima Hubbi, 2025)
Tropical peatland forests in Central Kalimantan, critical global carbon stores, are severely degraded and now act as major greenhouse gas sources due to drainage and fires. This study aimed to evaluate the ecological effectiveness and climate resilience of Assisted Natural Regeneration (ANR) for restoring the hydrological functions and biodiversity of these degraded ecosystems. A field experiment was established across 100 hectares, where the ANR method involved canal blocking to rewet the peat and selective planting of native pioneer species, monitored against control plots over five years. The results showed significant and rapid recovery. Canal blocking successfully raised the water table by an average of 40 cm, drastically reducing fire risk. Furthermore, native tree species richness in ANR plots was over 200% higher than controls, with canopy closure reaching 60%. ANR is highly effective, cost-efficient, and climate-resilient, providing a scalable model that prioritizes rewetting and facilitates natural successional pathways to restore critical ecosystem functions and secure long-term carbon storage.